Studies on the Phthalidation of Heteroarenes: A Facile Preparation of 3-(Heteroaryl)phthalides via Triflic Acid Mediated Phthalidation - Nandakumar, Meganathan; Sankar, Elumalai; Mohanakrishnan, Arasambattu K. (Synlett, 2014)
A triflic acid mediated heteroarylation of phthalaldehydic acid in 1,2-dichloroethane at reflux temperature leads to the formation of 3-heteroarylphthalides. This method for the phthalidation of heteroarenes can be utilized for the successful preparation of mono-, bis- and tris-heteroarylphthalides.
Keywords: triflic acid; heteroarylation; 3-heteroarylphthalides; Brønsted acid; Lewis acid